2018
DOI: 10.1159/000487814
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Pathological Response to Pembrolizumab following ex vivo Liver Resection in a Patient with Colorectal Liver Metastases

Abstract: Advances in the systemic treatment of stage IV colorectal cancer with liver metastases has offered improved survival rates for patients who otherwise face a dismal prognosis. However, a pathologically complete response (PCR) to chemotherapy for colorectal liver metastases is still rare, and its significance is not fully understood. In this case report, we describe a patient who achieved PCR after neoadjuvant immunotherapy with pembrolizumab and a left hepatectomy using an ex vivo resection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…2018 Apr 5;63(2):90–94. [ 16 ] 10 28 F S Wt Mut Por N.A FOLFOX + pembro 2 m 1 Colon, liver, LN N.A FoundationOne Clin Colorectal Cancer. 2018 Jun;17(2):e229-e232.…”
Section: Discussionmentioning
confidence: 99%
“…2018 Apr 5;63(2):90–94. [ 16 ] 10 28 F S Wt Mut Por N.A FOLFOX + pembro 2 m 1 Colon, liver, LN N.A FoundationOne Clin Colorectal Cancer. 2018 Jun;17(2):e229-e232.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint blockade has also been discussed as a neoadjuvant strategy, although studies have reported only a few cases. One case report had shown significant benefits when pembrolizumab was administered in the neoadjuvant setting in a Lynch syndrome patient, who after that qualified for surgical resection [108]. A retrospective study on two patients with locally advanced CRC has shown that nivolumab in the neoadjuvant setting can induce complete responses, either as a single treatment option or followed by surgery [109].…”
Section: Neoadjuvant Settingmentioning
confidence: 99%
“…Due to the low incidence of dMMR or MSI-H in CRC patients, substantial data to support their use in CLM are currently unavailable. A few case reports showed notable response to checkpoint inhibitors [ 46 , 47 ]. In a patient with Lynch syndrome (MSI-H) and CLM treated with neoadjuvant pembrolizumab, a pathologic complete response (CR) was achieved [ 46 ].…”
Section: Immune Checkpoint Inhibitors In Colorectal Liver Metastasesmentioning
confidence: 99%
“…A few case reports showed notable response to checkpoint inhibitors [ 46 , 47 ]. In a patient with Lynch syndrome (MSI-H) and CLM treated with neoadjuvant pembrolizumab, a pathologic complete response (CR) was achieved [ 46 ]. Two patients with locally advanced rectal cancer had dMMR, Lynch syndrome and high tumor mutation burden (TMB) [ 47 ].…”
Section: Immune Checkpoint Inhibitors In Colorectal Liver Metastasesmentioning
confidence: 99%